Systemic Hemodynamic and Myocardial Contractile and Metabolic Impairments in Severe Thermal Injury in the Experiment and Their Correction - M. A. Goldzon; V. T Dolgikh; A. O. Girsh (Общая реаниматология)
Objective: to experimentally reveal the optimal infusion therapy option for systemic hemodynamics, contractility and metabolism of the isolated rat heart in the early period of severe thermal injury. Material and methods. Experiments were carried out on 124 outbred albino male rats anesthetized with Nembutal (50 mg/kg intraperitoneally) to study myocardial contractility and metabolism of burnt animals, by applying an isolated isovolumically contacting heart specimen. Thermal injury was simulated by the contact method using the copper plates heated up to 60°C. Skin contact with the thermal agent lasted 15 seconds. Results. The parameters of systemic hemodynamics and myocardial contractility and metabolism of the isolated heart were found to be improved during infusion therapy performed in the early period of severe thermal injury. The best effect was obtained by infusion therapy combining isotonic sterofundin solution and venofundin solution, as well as isotonic sterofundin and gelofusine. Key words: thermal injury, cardiovascular system, infusion therapy.